Staffing strategies in multinational enterprises - Kalugina, Daria (2018)
This paper aims to create an integrated approach to global staffing, which develop the diverse perspectives on the key areas of global staffing and help to make connections among different topics. In theoretical part the author aims to identify models of staffing the MNE, traditional and alternative forms of global staffing and ways of composing the international staff, including international talent management, cross-cultural training and the position of women in management. The latest concepts and activities of global staffing are presented in the practical part of this paper and are discussed in relation to recent developments in international business, in order to help to relate the theoretical findings to what is currently happening in the real multinational enterprise.